2008
DOI: 10.1007/s00535-008-2169-6
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal function worsens with long duration of diabetes

Abstract: Gastroesophageal reflux and esophageal motility disorders worsened with long duration of diabetes. These esophageal dysfunctions should be considered in patients with long-standing diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
(74 reference statements)
0
27
0
Order By: Relevance
“…Several studies showed that disease duration of diabetes [117,120] and the presence of diabetic neuropathy [119,120] were associated with GERD. Because esophageal motility disorder and abnormal acid reflux in diabetic patients are associated with diabetic motor neuropathy [122] and such esophageal dysfunction is worsened with long disease duration [123], esophageal dysfunction may result in a higher prevalence of GERD in diabetic patients.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Several studies showed that disease duration of diabetes [117,120] and the presence of diabetic neuropathy [119,120] were associated with GERD. Because esophageal motility disorder and abnormal acid reflux in diabetic patients are associated with diabetic motor neuropathy [122] and such esophageal dysfunction is worsened with long disease duration [123], esophageal dysfunction may result in a higher prevalence of GERD in diabetic patients.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…This was relevant with others' findings which showed GERD was more prevalent in DM patients than non-DM patients. 4,13,14 Nonetheless, GERD in this study was less prevalent than GERD in DM patients in United States (40.8% in DM population vs 18.1-27.8% in its general population). 15,29 It might be caused by higher mean BMI in that study (32 ± 7.2 kg/m 2 ) 15 than the BMI in our study (24.07 ± 4.32 kg/m 2 ), resulting in worse GERD symptoms attributable to the co-morbidity.…”
Section: Discussionmentioning
confidence: 46%
“…4,[12][13][14][15] Studies conducted in various countries have shown that GERD was a frequent complication in approximately 23-29% of DM patients and reached up to half of total diabetes cases in New Jersey, United States. [15][16][17][18][19][20] Another complexity of DM in the case of GERD is that DM will give poor prognostic effect to the latter since: (1) DM will reduce the effectiveness of acid-suppression therapy, which is the mainstay therapy of GERD 21 and; (2) DM increases the occurrence of Barrett's esophagus and esophageal cancer.…”
mentioning
confidence: 99%
“…Thank you very much for your valuable comments on our article 1 . Autonomic neuropathy is a common complication of diabetes mellitus.…”
Section: Authors' Replymentioning
confidence: 99%